2018
DOI: 10.1016/j.ceramint.2017.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted hydrothermal synthesis followed by heat treatment: A new route to obtain CaZrO3

Abstract: CaZrO 3 nanoparticles were obtained by a new synthesis route: nucleation using the microwave-assisted hydrothermal method (MAH) and crystallization by heat treatment. Structural characterization by X-ray diffraction (XRD) was performed for the synthesized material and after heat treatment at 700, 800, 900, 1000 and 1200°C. At 800°C, the lakargite phase crystallization (CaZrO 3) starts and portions of the non-stoichiometric calciumzirconium oxide phase were observed by XRD and Raman spectroscopy. A residual CaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…9(a) shows the bandgaps of ANiO 3 (O- Pnma ) (A = Eu, Gd, Tb, Dy, Yb, La, Tm, Nd, Sm), EuBO 3 (O- Pbnm ) (B = Zr, Hf), EuTiO 3 (C- Pm 3̄ m ), DNbO 3 (O- Pnma ) (D = Ag, Ba, Ca, Sr, Eu, K, Na), SrTM 1 O 3 (C- Pm 3̄ m ) (TM 1 = Hf, Zr, Ti), KTaO 3 (C- Pm 3̄ m ), LaTM 2 O 3 (O- Pnma ) (TM 2 = Al, Sc, Fe, Cr, Ti, Ga, Co), SrTcO 3 (O- Pnma ), NaOsO 3 (O- Pbca ), MSnO 3 (R- R 3 c ) (M = Hg, Mg, Zn, Fe, Mn), NiSnO 3 (C- Pm 3̄ m ), SrNiO 3 (C- Pm 3̄ m ), BaSnO 3 (C- Pm 3̄ m ), CaSnO 3 (O- Pnma ), CoSnO 3 (O- Pnma ), TiSnO 3 (T- I 4/ mcm ), MnTiO 3 (R- R 3 c ), PbTiO 3 (T- I 4/ mcm ), CaZrO 3 (O- Pnma ), and BaFeO 3 (C- Pm 3̄ m ). As can be seen, there is good agreement in the bandgaps between our calculations and the experimental data and other reported HSE06 and G 0 W 0 data, 31–52 which demonstrates the accuracy of our method.…”
Section: Methodssupporting
confidence: 85%
“…9(a) shows the bandgaps of ANiO 3 (O- Pnma ) (A = Eu, Gd, Tb, Dy, Yb, La, Tm, Nd, Sm), EuBO 3 (O- Pbnm ) (B = Zr, Hf), EuTiO 3 (C- Pm 3̄ m ), DNbO 3 (O- Pnma ) (D = Ag, Ba, Ca, Sr, Eu, K, Na), SrTM 1 O 3 (C- Pm 3̄ m ) (TM 1 = Hf, Zr, Ti), KTaO 3 (C- Pm 3̄ m ), LaTM 2 O 3 (O- Pnma ) (TM 2 = Al, Sc, Fe, Cr, Ti, Ga, Co), SrTcO 3 (O- Pnma ), NaOsO 3 (O- Pbca ), MSnO 3 (R- R 3 c ) (M = Hg, Mg, Zn, Fe, Mn), NiSnO 3 (C- Pm 3̄ m ), SrNiO 3 (C- Pm 3̄ m ), BaSnO 3 (C- Pm 3̄ m ), CaSnO 3 (O- Pnma ), CoSnO 3 (O- Pnma ), TiSnO 3 (T- I 4/ mcm ), MnTiO 3 (R- R 3 c ), PbTiO 3 (T- I 4/ mcm ), CaZrO 3 (O- Pnma ), and BaFeO 3 (C- Pm 3̄ m ). As can be seen, there is good agreement in the bandgaps between our calculations and the experimental data and other reported HSE06 and G 0 W 0 data, 31–52 which demonstrates the accuracy of our method.…”
Section: Methodssupporting
confidence: 85%
“…CaZrO 3 presents at room temperature in the orthorhombic Pcmn (a À a À c + using Glazer notation 51 ), with CaZrO 3 reported to remain orthorhombic <2023 K prior to a transition to cubic symmetry. 52,53 SrZrO 3 takes the Pbnm (a À a À c + ) structure, with temperature induced phase transitions investigated by various groups. [54][55][56] Most recently Hasegawa et al 57 revisited the SrZrO 3 system and reported transitions to Ibmm (a À a À c 0 ) at 1042 K, I4/mcm (a 0 a 0 c À ) at 1119 K and to Pm 3m (a 0 a 0 a 0 ) at 1375 K. BaZrO 3 has the aristotype perovskite structure of Pm 3m (a 0 a 0 a 0 ), with no temperature related phase-transitions reported within the literature from 10 K to 1273 K. [58][59][60] Both space groups Pcmn and Pbnm are non-stand settings of Pnma (space group 62), however, within this work we refer to the most commonly used settings within the literature.…”
Section: Introductionmentioning
confidence: 99%
“…First, the Raman spectra of FC and CZ were studied as references under different temperatures (Figure a,b). In the CO 2 capture step, the Raman signal of the CZ sample showed a band at 711 cm –1 attributed to the vibrations of Zr–O bonds in CaZrO 3 . , Peaks for nonstoichiometric phase vibration modes, such as the peak at 141 cm –1 , were attributed to the CaZrO 3 phase . Peaks at 133, 240, and 694 cm –1 were ascribed to Fe–O vibrations in FC .…”
Section: Resultsmentioning
confidence: 98%
“…39,40 Peaks for nonstoichiometric phase vibration modes, such as the peak at 141 cm −1 , were attributed to the CaZrO 3 phase. 41 Peaks at 133, 240, and 694 cm −1 were ascribed to Fe−O vibrations in FC. 42 Moreover, the peak at 1079 cm −1 was attributed to the symmetric stretching of CO 3 2− on the CaO surface.…”
Section: Acs Sustainablementioning
confidence: 99%